2010
DOI: 10.4103/0972-6748.90337
|View full text |Cite
|
Sign up to set email alerts
|

Perception of violence against women among future health professionals in an industrial township

Abstract: Background:There is a growing concern that medical education does not prepare the future health professional to effectively deal with violence against women. Against this background, the present study was undertaken.Aims:To elicit perception of violence against women among medical and nursing students, and study the association of these perceptions with certain demographic and social variables.Settings and Design:The study was conducted among students of a Medical College and a Nursing College both located at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Sabancıoğulları et al found that students wanted to receive training and have more knowledge relevant to violence against women. Another study of students and nurses found that almost all of the participants had insufficient knowledge of violence against women, and they requested training on this subject …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sabancıoğulları et al found that students wanted to receive training and have more knowledge relevant to violence against women. Another study of students and nurses found that almost all of the participants had insufficient knowledge of violence against women, and they requested training on this subject …”
Section: Discussionmentioning
confidence: 99%
“…Another study of students and nurses found that almost all of the participants had insufficient knowledge of violence against women, and they requested training on this subject. 11,14,17,19,30,31 The average pretest and posttest scores on the attitude towards violence scale among students in the experimental and control groups were compared, and the posttest averages of students in the experimental group were lower than the pretest averages. In other words, there was a greater decrease in traditional attitudes towards violence among students who took the course on violence against women than among the students who did not take the course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a specific professional background is essential in detecting seemingly invisible and unsuspected gender violence [ 35 , 36 , 37 ], as well as when assisting men in acknowledging the causes and effects of their actions and inviting them to find new strategies to express their negative emotions [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The interviewers were able to comprehend the innovativeness and specificity of the interviewees’ contributions, allowing them to add and expand upon novel research findings. They were required to demonstrate reflective competence, to suspend any judgments, and to maintain an active and stimulating attitude toward the interlocutor [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: The Researchmentioning
confidence: 99%